2001
DOI: 10.1038/35082583
|View full text |Cite|
|
Sign up to set email alerts
|

Roles of tumour localization, second signals and cross priming in cytotoxic T-cell induction

Abstract: The vertebrate immune system has evolved to protect against infections that threaten survival before reproduction. Clinically manifest tumours mostly arise after the reproductive years and somatic mutations allow even otherwise antigenic tumours to evade the attention of the immune system. Moreover, the lack of immunological co-stimulatory molecules on solid tumours could result in T-cell tolerance; that is, the failure of T cells to respond. However, this may not generally apply. Here we report several import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
387
1
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 455 publications
(409 citation statements)
references
References 27 publications
(1 reference statement)
13
387
1
6
Order By: Relevance
“…Six weeks later, we confirmed that CXCR3 protein continued to be expressed in the transplanted cells by immunohistochemistry (Figure 4a), and examined macroscopically metastatic foci of the para-aortic LNs using GFP fluorescence. Interestingly, the mice inoculated not only with DLD-1-CXCR3 cells, but also with DLD-1-EV cells showed macroscopic enlargement of the para-aortic LNs, which reflects that sensitized immune cells can reach LNs and cause proliferative reactions (Ochsenbein et al, 2001). However, under a fluorescence dissection microscope, we found that DLD-1-CXCR3 cells metastasized to LNs with a significantly higher frequency than DLD-1-EV (Figure 4b).…”
Section: Cxcr3 In Colon Cancer Metastasis To Lymph Nodes K Kawada Et Almentioning
confidence: 87%
“…Six weeks later, we confirmed that CXCR3 protein continued to be expressed in the transplanted cells by immunohistochemistry (Figure 4a), and examined macroscopically metastatic foci of the para-aortic LNs using GFP fluorescence. Interestingly, the mice inoculated not only with DLD-1-CXCR3 cells, but also with DLD-1-EV cells showed macroscopic enlargement of the para-aortic LNs, which reflects that sensitized immune cells can reach LNs and cause proliferative reactions (Ochsenbein et al, 2001). However, under a fluorescence dissection microscope, we found that DLD-1-CXCR3 cells metastasized to LNs with a significantly higher frequency than DLD-1-EV (Figure 4b).…”
Section: Cxcr3 In Colon Cancer Metastasis To Lymph Nodes K Kawada Et Almentioning
confidence: 87%
“…However, tumor stroma may hinder T cell priming by sequestering antigenic tumor cells, thus preventing them from reaching the DLN to directly prime a T cell response [17]. In such an event, cross-presentation by professional APCs, often DCs, from the tumor tissues becomes a major pathway for naĂŻve T cells to be primed tumor antigens.…”
Section: Hindrance Of Priming By Tumor Stromamentioning
confidence: 99%
“…Moreover, the priming and activation of antigen‐specific CD8 + CTLs required co‐stimulatory signalling via CD80 and CD86 10. Hence, CD8 + CTLs, which are tumour‐specific, can be primed and activated by tumour‐antigen‐loaded activated DEC‐205 + DCs expressing co‐stimulatory molecules 11, 12…”
Section: Introductionmentioning
confidence: 99%